A-162 Neuropsychological Functioning in Migraine: A Meta-Analysis. (17th August 2022) - Pizer, Jasmin H; Aita, Stephen L; Myers, Melissa A; Hawley, Nanako A; Ikonomou, Vasilios C; Brasil, Kyle M; Hernandez, Katherine A; Pettway, Erika C; Hill, Benjamin D
Abstract: Objective: Migraine refers to recurrent, unilateral headache attacks, lasting 4-72 hours, that have a pulsating quality. A meta-analysis was conducted comparing cognition on clinical measures between individuals with migraine and healthy controls. Data Selection: We searched the University of South Alabama Libraries' OneSearch and PubMed using a uniform search-strategy to locate original research comparing cognition between migraine and control samples. Analyses were modeled under random effects. Hedge's g was used as a bias-corrected estimate of effect size. We assessed between-study heterogeneity using Cochran's Q and I2. Data Synthesis: The initial search interval spanned inception–May 2021 and yielded 6692 results. Fifty-two studies were analyzed (migraine n=5324, control n=16540). Meta-analysis showed a significant combined effect size of migraine across all studies (g=-0.37, p<.001), with high heterogeneity (Q=329.84, p<.001, I2=84.54). Trim-and-fill procedure estimated 0 studies to be missing due to publication bias (adjusted g=-0.37, Q=329.84). Within-domain effects of migraine were: Executive Functioning=-0.40, Global Cognition/Orientation=-0.20, Language=-0.30, Learning/Memory=-0.24, Motor=-0.09, Processing Speed=-0.42, Screener=-0.50, Simple/Complex Attention=-0.35, and Visuospatial/Construction=-0.36. Heterogeneity was moderate to high within domains. Meta-regressions indicated education and disease duration were not related to effect sizes. Age and gender were related to effect sizes such that studies with older and higher percentage of female clinical participants yielded greater (negative) differences. Conclusions: Individuals with migraine consistently demonstrated lower performances on neuropsychological tests compared to controls. Effect sizes were generally small in strength, with largest effects in Executive Functioning, Processing Speed, and Screeners. This quantitative summary indicates that, through use of neuropsychological tests, individuals with migraine experience difficulties in multiple aspects of cognition.